Crise financeira: o caso japonês - Fraga, Jefferson Souza [UNESP]; Strachman, Eduardo (Nova Economia, 2013)
This paper aims to analyze the experience of Japan after the collapse of speculative bubbles in assets and the banking crisis in the 1990s. An analysis about the effectiveness of fiscal and monetary policy is conducted and the measures taken with respect to the banking sector are also discussed in this paper. The Japanese financial crisis experience suggests that the nature, speed and order in which the government implements measures determine, in large part, the magnitude and cost of the crisis. Therefore, in hindsight, it can be said that the following tasks were necessary: 1) recapitalize the banking sector; 2) restore credit; and 3) reinvigorate the economic activity through appropriate fiscal measures.

Analisar a experiência do Japão, após os colapsos das bolhas especulativas dos ativos e a crise bancária no país, na década de 1990, é o objetivo do presente trabalho. Analisa-se a eficácia das políticas fiscais e monetárias adotadas e discutem-se as medidas tomadas com relação ao setor bancário. A experiência da crise financeira japonesa sugere que a natureza, a velocidade e a ordem em que o poder público implementa medidas podem determinar a magnitude e o custo da crise. Portanto, em retrospectiva, percebe-se que era necessário realizar as seguintes tarefas: 1) recapitalizar o setor bancário; 2) restaurar o crédito; e 3) revigorar a atividade econômica, por meio de medidas fiscais adequadas.
Keywords: Japão; colapsos de bolhas especulativas; crise financeira; Apolítica; econômica; Japan; collapse of speculative bubbles; financial crisis; economic policy